PEMANFAATAN INOVASI PRODUK HUTAN MANGROVE SEBAGAI PEWARNA ALAMI KAIN BATIK TRADISIONAL MALANG UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA TAMBAKREJO KABUPATEN MALANG - Lilik Sulistyowati; Mohammad Fauzi Hafa; Andilopa Ginting; Darwiyati Darwiyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The community of Tambakrejo village needed an assistance regarding innovation and advertising of products derived from mangrove forest, as well as waste management in mangrove forest areas. To support the use of products from mangrove forests this research describes the form of collaborative cooperation between elements of the Quadruple Helix which aims to: (1) develops mangrove products as natural dyes for Malang traditional batik textile, (2) Knowing the limitations and difficulties in the manufacture of mangrove-based product felt by the community, (3) Describe the Quadruple Helix Collaboration strategy in encouraging mangrove-based product to improve the economy of the community in Tambakrejo Village. This quadruple helix model is considered effective because it provides additional opportunity for participation for all existing stakeholders in the area, expressly the community who sees it exclusively as an object of policy-making process. Data collection used a qualitative descriptive approach. The data analysis method uses the Miles and Huberman interactive analysis model. Our findings showed by utilizing Quadruple helix collaborating strategy trial is used in the first model, thus making Universitas Terbuka as a driving force to encourage innovation due to the fact that there was not any community-based creative industry center in Tambakrejo Village. In addition to the fact that the community had never received funding to afford a formal training in the manufacture of mangrove-based product. Mangrove stems, fruits, leaves and roots are used as a raw material for producing natural dye for batik textiles. The collaboration was carried out between the government (head of the village), academics (Universitas Terbuka), private entity (LPK Nawata Korea Center), and 12 member of the community of Tambakrejo. This approach has succeeded in encouraging the community to kick-start innovation in the development of mangrove-based products as natural dyes for Malang traditional batik textile to improve the economy of the community in Tambakrejo village.